Mobility and agility with an improved sight - Ribeiro, A. Fernando (2009)
This paper briefly describes the main changes on Minho Team robots since the last RoboCup participation. Work has been carried out on the robots in order to constantly improve their capabilities, based on the experience from previous participations. The team stopped for one year in order to implement structural changes and to add new features. The main topics to deal in this paper are related to structural changes of the robot, the in-house development of a robust and configurable motor driver used for each of the three motors and the improvement in the robot head and vision system for a better sight. Also on this paper a description of the whole software changes and implementation, and the use of Object Oriented paradigm for robot programming.